ROS enhances the cytotoxicity of cisplatin by inducing apoptosis and autophagy in tongue squamous cell carcinoma cells. (May 2020) - Xue, Dan-Feng; Pan, Shu-Ting; Huang, Gan; Qiu, Jia-Xuan
Highlights: Down-regulation of intracellular ROS decreases the cytotoxicity of cisplatin in TSCC cells. Down-regulation of intracellular ROS decreases the apoptosis induced by LPS combination with CDDP in CAL27/CDDP cells. Down-regulation of intracellular ROS decreases the autophagy induced by LPS combination with CDDP in CAL27/CDDP cells. Down-regulation of intracellular ROS attenuates apoptosis and autophagy via regulating the p38MAPK/mTOR pathway in CAL27/CDDP cells. Abstract: Cisplatin is one of the most widely used anticancer agents for patients with tongue squamous cell carcinoma (TSCC), but its efficacy is limited by chemoresistance. Accumulated evidence has demonstrated that reactive oxygen species (ROS) plays a critical role in multiple tumor chemotherapy resistance. In the present study, we aimed to investigate the role of ROS in cisplatin resistance of TSCC and explore its underlying molecular mechanism in vitro . Our results showed that pre-treatment with ROS scavenger N-acetylcysteine reduced cisplatin-induced cytotoxicity, autophagy, and apoptosis in TSCC cells. Down-regulation of intracellular ROS attenuated apoptosis and autophagy of TSCC cisplatin-resistant CAL27/CDDP cells by reversing the inhibition of p38MAPK/mTOR pathway. Taken together, these findings suggest that down-regulation of intracellular ROS reduces the cytotoxicity of cisplatin by inhibiting apoptosis and autophagy in TSCC cells involving p38MAPK/mTOR mediated pathway. Low intracellular ROS levels may be one of the main mechanisms of cisplatin resistance in TSCC.